Marketing Budgeting, Marketing Activities, and Distributor Loyalty: the Mediating Effect of Brand Equity - Gregorius Wahyu Kurniawan; Firdaus Basbeth; Assoc Prof. Dr. Leonnard Ong, SE, M. Comm (ADI Publisher, 2020)
In reaching their customers, the producer of fast-moving consumer goods (Keller, 1993) use distributors' channels to reach their end-user. Despite having a strong brand globally, with 9.04 bio USD of brand value (2020), the company experienced steady growth with higher marketing budget spending from 2017 to 2019. The trend of operating incomes has not improved. The effect of brand equity on loyalty in the B2B segment has not been conclusive. The study aims to find out the level of distributor loyalty, the effect of marketing activity, marketing budgeting, and brand equity on distributor loyalty. The research strategy was a survey, conducted with a quantitative method, with 65 distributors as respondents. The data was analyzed with a descriptive statistic and hypotheses were tested using SmartPLS3. The result has shown that the level of distributor loyalty was good, there was a positive significant effect of marketing activity on loyalty, a positive significant effect of marketing activity on brand equity, and a positive significant effect of brand equity to distributor loyalty. However, there was no effect of marketing budgeting to brand equity. The study gave a contribution to the industrial market segment or B2B marketer, for them to be able to invest marketing activity spending into the right marketing activity mix, suited to the market condition to achieve a better return of investment. Building brand equity in the industrial market segment is as important as consumer market. However, marketers shall be able to differentiate the approach, since the brand equity measures for the industrial market segment are different as compared to the consumer market.